Hadith #4799 - Sunan Abi Dawud - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Harithh bin Wahb al-Khza'y; Ma'bad bin Khalid al-Jadli معبد بن خالد الجدلي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Uthman bin Muhammad; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Abi Dawud)
The Prophet (ﷺ) said: There is nothing heavier than good character put in the scale of a believer on the Day of Resurrection. Abu al-Walid said: I heard ‘Ata al-Kaikharani say: Abu Dawud said: His name is ‘Ata b. Ya’qub. He is the maternal uncle of Ibrahim b. Nafi’. He is called Kaikharani or Kukharani.
Grade: Sahih

Hadith #5043 - Sunan Abi Dawud - Aban bin Tghlb أبان بن تغلب; Asim al-Ahwal عاصم الأحول; Ma'bad bin Khalid al-Jadli معبد بن خالد الجدلي; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي (Sunan Abi Dawud)
The Messenger of Allah (May peace be upon him) got up at night, fulfilled his need and washed his face and hand and then slept. Abu Dawud said: that is to say, he urinated
Grade: Sahih